Targeting copper in cancer therapy: 'Copper That Cancer'. Issue 11 (27th August 2015) - Denoyer, Delphine; Masaldan, Shashank; La Fontaine, Sharon; Cater, Michael A.
Abstract : Copper coordination compounds target copper in cancer by diverse mechanisms. Abstract : Copper is an essential micronutrient involved in fundamental life processes that are conserved throughout all forms of life. The ability of copper to catalyze oxidation–reduction (redox) reactions, which can inadvertently lead to the production of reactive oxygen species (ROS), necessitates the tight homeostatic regulation of copper within the body. Many cancer types exhibit increased intratumoral copper and/or altered systemic copper distribution. The realization that copper serves as a limiting factor for multiple aspects of tumor progression, including growth, angiogenesis and metastasis, has prompted the development of copper-specific chelators as therapies to inhibit these processes. Another therapeutic approach utilizes specific ionophores that deliver copper to cells to increase intracellular copper levels. The therapeutic window between normal and cancerous cells when intracellular copper is forcibly increased, is the premise for the development of copper-ionophores endowed with anticancer properties. Also under investigation is the use of copper to replace platinum in coordination complexes currently used as mainstream chemotherapies. In comparison to platinum-based drugs, these promising copper coordination complexes may be more potent anticancer agents, with reduced toxicity toward normal cells and they may potentially circumvent the chemoresistance associated with recurrent platinum treatment. In addition, cancerous cells can adapt their copper homeostatic mechanisms to acquire resistance to conventional platinum-based drugs and certain copper coordination complexes can re-sensitize cancer cells to these drugs. This review will outline the biological importance of copper and copper homeostasis in mammalian cells, followed by a discussion of our current understanding of copper dysregulation in cancer, and the recent therapeutic advances using copper coordination complexes as anticancer agents.